2015
DOI: 10.1002/cyto.a.22669
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence triggering: A general strategy for enumerating and phenotyping extracellular vesicles by flow cytometry

Abstract: Plasma contains cell-derived extracellular vesicles (EVs) which participate in various physiopathological processes and have potential biomedical applications. Despite intense research activity, knowledge on EVs is limited mainly due to the difficulty of isolating and characterizing sub-micrometer particles like EVs. We have recently reported that a simple flow cytometry (FCM) approach based on triggering the detection on a fluorescence signal enabled the detection of 503 more Annexin-A5 binding EVs (Anx51 EVs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
139
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(171 citation statements)
references
References 55 publications
(88 reference statements)
8
139
0
Order By: Relevance
“…Fluorescence triggering Recently, several groups have shown that the sensitivity of flow cytometers can be increased by triggering on fluorescence [2,3,23,41,42]. Clearly, fluorescence triggering is a valid approach, although it is hampered by two problems.…”
Section: Recent Methods For Detecting Single Evsmentioning
confidence: 99%
“…Fluorescence triggering Recently, several groups have shown that the sensitivity of flow cytometers can be increased by triggering on fluorescence [2,3,23,41,42]. Clearly, fluorescence triggering is a valid approach, although it is hampered by two problems.…”
Section: Recent Methods For Detecting Single Evsmentioning
confidence: 99%
“…Appropriate calibration using commercially available reagents and well documented protocols allows us to report surface marker intensities in absolute units of MESF, an important step in comparing data over time and between labs. Brisson and colleagues (40,42) have estimated that a 150 nm EV covered to saturation with annexin V, would bear only approximately 2,500 molecules per vesicle while a 100 nm EV might bear only approximately 1,000 molecules, which is near the resolution limit of a typical commercial flow cytometer. Our high sensitivity system has a resolution limit of approximately 240 MESF of fluorescein, which provides improved sensitivity, but many less abundant vesicle markers might be present in number below this limit, making it important to calibrate the fluorescence measurements and report particle intensities in absolute units.…”
Section: Discussionmentioning
confidence: 99%
“…This approach has the potential to offer better separation from background noise and is less likely affected by aggregation of particles and might detect particles as low as 100-200 nm. 51, 52 The addition of imaging to FCM can also significantly increase the sensitivity of MP detection. 53,54 Imaging flow cytometry (IFCM) can also provide morphologic confirmation and the ability to distinguish true single events from aggregates and cell debris (Figure 2).…”
Section: Overview Of Detection Techniques Of Evsmentioning
confidence: 99%